Patterns of Presentation of SARS-CoV-2 Infection in Children. Experience at the Italian Epicentre of the Pandemic - Mazza, Angelo; Di Giorgio, Angelo; Martelli, Laura; Pelliccia, Ciretta; Pinotti, Moira Alessandra; Quadri, Vera; Verdoni, Lucio; Decio, Alice; Ruggeri, Maurizio; D'Antiga, Lorenzo (Frontiers in Pediatrics, 2021)
Background: COVID-19, a disease caused by the new coronavirus SARS-CoV-2, spread worldwide, and Bergamo was one of the most affected areas in Europe. Following the first outbreak, more than half of the population of the Bergamo province had been infected. We aimed to describe the patients admitted to our unit shortly after the first outbreak. Methods: we retrospectively reviewed the notes of all paediatric patients diagnosed with COVID-19. We enrolled patients with positive swabs or serology and classified them based on the pattern and the timing of presentation after the first outbreak. This setting was considered a reliable reflection of the consequences of unmitigated SARS-CoV-2 circulation. Results: We diagnosed 35 patients over a three-month period and we identified 6 patterns presenting in two temporal phases: Early phase, Group 1 (median of 20 days from epidemic start, IQR: 15-27): neonatal sepsis (n.7), pneumonia (n.5), flu-like symptoms (n.2). Late phase, Group 2 (59:51-66 days, p<0.001): MIS-C (n.18), neurological manifestations (n.3). Group 1 differed from Group 2 for younger age (1 vs 8 years, p=0.02), lower C-reactive protein (0.9 vs 16.6 mg/dl, p=0.008), procalcitonin (0.16 vs 7.9 ng/ml, p=0.008) and neutrophil count (3,765 vs 6780/μl, p=0.006), higher rate of positive swabs (14/14 vs 9/21, p<0.001), higher lymphocyte count (2,000 vs 930/μl, p=0.006) and platelet count (323,000 vs 210,000/μl, p=0.009). Conclusions: Following an outbreak of unmitigated SARS-CoV-2 diffusion, infected children may present with clinical patterns suggesting two temporal clusters, the first characterised by markers of direct viral injury, the second suggesting an immune-mediated disease.